Effect of Diabetic Gymnastics on Blood Glucose Levels in Type 2 Diabetes Mellitus Patients: A Quasi-experimental Study - Prasetia, Arif Budi; Cahyati, Yanti; Riyana, Asep (Journal of Pubnursing Sciences, 2025)
Background: Diabetes mellitus is a non-communicable disease characterized by persistently elevated blood glucose levels exceeding the normal range of 70–150 mg/dL. Effective diabetes management consists of five key components: education, nutritional therapy, physical activity (including diabetic exercises), pharmacological treatment, and regular blood glucose monitoring. Diabetic exercise, when tailored to an individual’s age and physical condition, can help lower blood glucose levels, enhance stamina, and maintain healthy body weight in individuals with type 2 diabetes mellitus. The recommended duration of diabetic exercise is at least 30 minutes per session, three to four times per week for adults, and 60 minutes with similar frequency for children and adolescents. Aim:  To analyze the effect of diabetic exercise (diabetes mellitus gymnastics) on blood glucose levels in patients with type 2 diabetes mellitus. Method: This study employed a quasi-experimental design using a one-group pretest–posttest approach. The sample consisted of 20 individuals diagnosed with type 2 diabetes mellitus, selected through purposive sampling based on predefined inclusion and exclusion criteria. Blood glucose levels were measured before and after the diabetic exercise intervention. Data were analyzed using the paired sample t-test to determine the statistical significance of the differences observed. Results: The findings revealed a significant reduction in blood glucose levels following the diabetic exercise intervention. The mean random blood glucose (RBG) level before the intervention was 202.85 mg/dL, and after the intervention, it decreased to 164.50 mg/dL, with a mean difference of 38.35 mg/dL. Statistical analysis using the paired t-test produced a significance value (2-tailed) of 0.000 (p < 0.05), indicating that diabetic exercise had a statistically significant effect in lowering average RBG levels among participants. Conclusion: This study demonstrates that diabetic exercise effectively reduces blood glucose levels in patients with type 2 diabetes mellitus. These findings support the integration of structured physical activity as a safe, feasible, and non-pharmacological intervention within diabetes management programs, particularly at the primary healthcare level.